Concurrent fatigue and postactivation potentiation during extended interval training in long-distance runners - Pedro Ángel Latorre-Román; Felipe García-Pinillos; Emilio José Martínez-López; Victor Manuel Soto-Hermoso (Universidade Estadual Paulista (UNESP), 2014)
The purpose of this study is to analyze acute effect of running extended interval training(EIT) on vertical jump (VJ) and handgrip strength (HS) performance in experienced endurance athletes. In order to analyze mechanical parameters of the VJ and HS between runs, sixteen experienced male athletes performed an EIT (4x3x400m). The results show that fatigue induced by EIT does not impair handgrip strength or VJ performance. A significant improvement (p< .05) was noted for VJ due to the postactivation potentiation (PAP) phenomenon. A positive correlation (r= .619, p= .011) was found between VJ and lactate. The results suggest that experienced long-distance runners can maintain their strength levels and, consequently, work capacity, despite the induced fatigue by the field training demand. Therefore, VJ performance during EIT can be used as an indicator of muscular adaptations to training and, together, with handgrip strength, become indicators of fatigue. These indicators allow proper prescription training routines.